2021
DOI: 10.1038/s41598-021-97788-1
|View full text |Cite
|
Sign up to set email alerts
|

Blunted emotion judgments of body movements in Parkinson’s disease

Abstract: Some of the behavioral disorders observed in Parkinson’s disease (PD) may be related to an altered processing of social messages, including emotional expressions. Emotions conveyed by whole body movements may be difficult to generate and be detected by PD patients. The aim of the present study was to compare valence judgments of emotional whole body expressions in individuals with PD and in healthy controls matched for age, gender and education. Twenty-eight participants (13 PD patients and 15 healthy matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(69 reference statements)
0
3
1
Order By: Relevance
“…We can therefore conclude that this effect is spared in PD and in AD patients, thus corroborating the studies carried out by Smith et al (2010) and Knopf et al (2005) with PD patients and Charlesworth et al (2014) and Borg et al (2018) with AD patients. Nevertheless, these results are somehow in disagreement with Bellot et al’s (2021) hypothesis of the embodied simulation deficit in PD patients. However, in their study, patients judged the valence of whole-body emotional expressions presented in videoclips, whereas, in the present study, patients performed themselves actions in order to memorize them, which implies quite different processes.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…We can therefore conclude that this effect is spared in PD and in AD patients, thus corroborating the studies carried out by Smith et al (2010) and Knopf et al (2005) with PD patients and Charlesworth et al (2014) and Borg et al (2018) with AD patients. Nevertheless, these results are somehow in disagreement with Bellot et al’s (2021) hypothesis of the embodied simulation deficit in PD patients. However, in their study, patients judged the valence of whole-body emotional expressions presented in videoclips, whereas, in the present study, patients performed themselves actions in order to memorize them, which implies quite different processes.…”
Section: Discussioncontrasting
confidence: 68%
“…These effects of congruency between performed action (i.e., flexion, extension) and subjective valence evaluation can be interpreted in favor of a bodily representation of emotional valence (Casasanto & Dijkstra, 2010; Förster & Stepper, 2000). Recently, Bellot et al (2021) have shown that PD patients judged the valence of whole-body emotional expressions (positive and negative) as less intense than elderly controls. The authors proposed that these results might suggest an impairment of embodied simulation of emotional expression in PD.…”
mentioning
confidence: 99%
“…Children with Moebius syndrome, a congenital inability to produce facial displays, exhibit alterations in the processing of observed facial expressions of others [71]. Patients with Parkinson's disease, which is characterized by reduced facial mimicry, exhibit impairments in the recognition of both facial [72] and bodily [73] emotional expressions relative to control subjects. Similarly, patients with schizophrenia exhibit a reduced ability to produce and recognize facial emotions [74], but notably, they can improve their recognition performance by undergoing specific training to mobilize their facial muscles for executing transitive actions [75]; conversely, blocking facial mimicry in healthy humans selectively impairs the recognition of emotion in not only facial, but also bodily expressions [76].…”
Section: Perception Of Bodily Actions and Action Planning During Soci...mentioning
confidence: 99%
“…In the fields of emotion psychology, affective neuroscience, and computer vision, such research often relies on datasets that comprise stimuli of pictures or videos of facial and bodily expressions of emotions. Yet, compared to the extensive existing research on the recognition of emotions from facial expressions (Byron et al, 2007;Elfenbein & Ambady, 2002;O'Boyle Jr et al, 2011;Rosete & Ciarrochi, 2005;Rubin et al, 2005;Scherer & Scherer, 2011;Walter et al, 2012;Zuskin et al, 2007), the bodily channel of emotional expression has received less empirical attention, despite important calls to extend emotion perception research to this domain (Aviezer et al, 2012;Bellot et al, 2021;de Gelder, 2006de Gelder, , 2009Keck et al, 2022;McCarty et al, 2017;Vaessen et al, 2018). Less stimulus materials are available, and available datasets suffer from limitations (discussed in, e.g., Christensen & Calvo-Merino, 2013;Christensen & Jola, 2015;Smith & Cross, 2022).…”
Section: Introductionmentioning
confidence: 99%